1999
DOI: 10.1111/j.1600-0838.1999.tb00237.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preexercise stretching on muscular soreness, tenderness and force loss following heavy eccentric exercise

Abstract: The present study sought to investigate the effects of preexercise stretching on delayed onset muscle soreness (DOMS), i.e. soreness, tenderness and loss of muscle force, that usually occurs after strenuous or unaccustomed eccentric exercise. Ten female volunteers performed 10 sets of 10 maximal isokinetic eccentric contractions for knee flexion with both legs after a 5‐min ergometer cycling warm‐up. Prior to the exercise for one leg, randomly chosen, 4×20 s of static stretching for the hamstring muscle group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 36 publications
(17 reference statements)
1
31
2
2
Order By: Relevance
“…The result of our study was similar to this study, but it was different from previous studies by High et al 25 , Johansson et al 26 . Additionally, pulsed ultrasound was used in the past for stable cavitation and microstreaming to heal injured muscles.…”
Section: -Hours After Exercisecontrasting
confidence: 46%
“…The result of our study was similar to this study, but it was different from previous studies by High et al 25 , Johansson et al 26 . Additionally, pulsed ultrasound was used in the past for stable cavitation and microstreaming to heal injured muscles.…”
Section: -Hours After Exercisecontrasting
confidence: 46%
“…Nine RCTs (Buroker & Schwane, 1989;Gulick et al, 1996;High et al, 1989;Johansson et al, 1999;Lund et al, 1998;McGlynn et al, 1979;Torres et al, 2007;Torres et al, 2005;Wessel & Wan, 1994) were found ( Table 4) that evaluated the effects of muscle stretching after exercise-induced muscle damage.…”
Section: Studies Includedmentioning
confidence: 99%
“…single stretching program before exercise (Johansson et al, 1999;Wessel & Wan, 1994); single stretching program after exercise (Gulick et al, 1996;High et al, 1989;Torres et al, 2007;Wessel & Wan, 1994); single stretching program before and repeated stretching program after exercise (High et al, 1989); and repeated stretching program after exercise (Buroker & Schwane, 1989;McGlynn et al, 1979). Therefore, the effect of stretching in the recovery of muscle function seems to fail regardless of when it is applied.…”
Section: Effect Of Stretchingmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim of stretching is to maintain or improve flexibility. It has also been suggested that stretching may prevent injury (1), reduce delayed onset muscle soreness (9), and performed chronically can enhance performance (10), though these claims are more controversial not least because the processes by which these effects may arise are complex. Nevertheless, it is widely accepted that flexibility is an important component of general fitness, and it is likely that there is a certain minimum range of motion required to safely and optimally perform a given activity.…”
Section: Introductionmentioning
confidence: 99%